2022
DOI: 10.1021/acsomega.2c05569
|View full text |Cite
|
Sign up to set email alerts
|

Nb/Starch-Doped ZnO Nanostructures for Polluted Water Treatment and Antimicrobial Applications: Molecular Docking Analysis

Abstract: Nb/starch-doped ZnO quantum dots (QDs) were prepared by a coprecipitation route. A fixed quantity of starch (st) and different concentrations (2 and 4%) of niobium (Nb) were doped in a ZnO lattice. To gain a better understanding of synthesized nanostructures, a systematic study was carried out utilizing several characterization methods. The goal of this research was to undertake methylene blue (MB) dye degradation with a synthetic material and also study its antibacterial properties. The phase structure, morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 87 publications
(165 reference statements)
0
6
0
Order By: Relevance
“…18 In the search for ZnO NPs with novel properties, doping with metals is a promising area where surface properties can be ne-tuned based on the target applications. 19 Several research groups, such as Vikal et al, 10 Ikram et al, 20 Mishra et al, 21 Ambedkar et al, 15 Kadhim et al, 22 Zelekew et al, 17 Liu et al, 1 and Kumar et al, 23 have prepared ZnO NPs doped with different metals, such as silver (Ag), copper (Cu), chromium (Cr), manganese (Mn), aluminium (Al) and magnesium (Mg), etc., via diverse approaches. However, the selection of dopants is based on the type of application coupled with the methodology adopted.…”
Section: Introductionmentioning
confidence: 99%
“…18 In the search for ZnO NPs with novel properties, doping with metals is a promising area where surface properties can be ne-tuned based on the target applications. 19 Several research groups, such as Vikal et al, 10 Ikram et al, 20 Mishra et al, 21 Ambedkar et al, 15 Kadhim et al, 22 Zelekew et al, 17 Liu et al, 1 and Kumar et al, 23 have prepared ZnO NPs doped with different metals, such as silver (Ag), copper (Cu), chromium (Cr), manganese (Mn), aluminium (Al) and magnesium (Mg), etc., via diverse approaches. However, the selection of dopants is based on the type of application coupled with the methodology adopted.…”
Section: Introductionmentioning
confidence: 99%
“…DNA gyrase is a class II topoisomerase that facilitates changes in the DNA helix . Substances the target DNA gyrase can have antimicrobial action and DNA gyrase has become a potential target for antimicrobial drug discovery . Molecular docking results indicated that ZnO had favorable binding interaction with DNA gyrase (subunit B: 4urm), and the estimated binding energy was −2.93 kcal/mol which suggested that ZnO has the potential to bind with the active sites of this protein and potentially inhibit its activity, which could contribute to its antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…This antibacterial application of metal oxide NPs has recently been reviewed by Naseem and Durrani . To support the study of the antibacterial response of different metal oxide composites, molecular docking studies gained importance through the investigation of protein–ligand interactions with the aim of highlighting amino acids of the targeted protein’s active site and supporting the hypothesis of a consequent inhibitory effect leading to a bactericidal observation. …”
Section: Introductionmentioning
confidence: 99%